The required number of trials for biomechanical analysis of a golf swing - Severin, A. C.; Barnes, S. G.; Tackett, S. A.; Barnes, C. L.; Mannen, E. M. (Sports Biomechanics, 2021)
The increasing interest in the biomechanical analysis of the golf swing warrants establishing the minimum number of trials required to obtain reliable data. Several such methods have been suggested previously for other movement tasks, and it has been shown that the number of required trials depends on the method used and on the task examined. This study aimed to compare three methods of reliability: a sequential average, intraclass correlations, and a modified version of the standard error of measurement (SEMind). Kinematic and kinetic data of 10 recreational golfers performing 15 shots with both a six-iron and a driver was collected using a ten-camera motion capture system and force platforms. Range-of-motion, velocity, joint moments, and ground reaction forces were extracted and analysed using the three methods. The sequential average method yielded the highest number of required trials (12), while the intraclass correlations and SEMind both resulted in lower numbers of required trials (4). Considering the variability between participants and strengths and limitations of the various methods, we conclude that 8 trials is sufficient for biomechanical analyses of a golf swing and recommend the SEMind method for determining how many swings should be collected.